If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 + -1t = -4 + t Add '4' to each side of the equation. -4 + 4 + -1t = -4 + 4 + t Combine like terms: -4 + 4 = 0 0 + -1t = -4 + 4 + t -1t = -4 + 4 + t Combine like terms: -4 + 4 = 0 -1t = 0 + t -1t = t Solving -1t = t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-1t' to each side of the equation. -1t + -1t = t + -1t Combine like terms: -1t + -1t = -2t -2t = t + -1t Combine like terms: t + -1t = 0 -2t = 0 Divide each side by '-2'. t = 0 Simplifying t = 0
| 3x+7=7x+15 | | 15/6=n/12 | | 0.6x+2=0.7+2 | | -10-7w-10=7-4w | | 4-3cot=1 | | 40=8(x-8) | | X^2-12X-4.5=0 | | P=2x+3 | | -8y=-6-9y | | -3(5+2x)=-2x+13 | | 8-(4x-12)=8x-(3x-2) | | 2-5f=-7f+10 | | 4+2y=10-4y | | 3/5=6n | | -j=j-8 | | -5x(4x-8y^2+4)= | | 10-6n=-6-10n | | 3b-11=3+b | | 7x-14=7(x+4) | | 5+10d=9d | | 6x-(10-2x)=3x+5 | | 9b+3=22 | | 18.9125-(1/4)= | | 9b+3=20 | | 9b+3=19 | | 2x^3-11x^2-10x+75=0 | | 9b+3=18 | | 9b+3=16 | | 4(t-3)+6t=5(2t+5)-12 | | 4x+3(2x-1)-4x=x | | a+4=a | | 4b+3=7 |